Neonatal hyperbilirubinaemia and its early outcome - Nepal, D.; Banstola, D.; Dhakal, A. K.; Mishra, U.; Mahaseth, C. (Journal of Institute of Medicine Nepal, 2010)
Introduction: Jaundice is an important cause of morbidity in the neonatal period, especially in the 1st week of life. our Objective of the study was to find out early outcome of babies admitted in Kanti Children Hospital with neonatal jaundice (NNJ) and its association with other co-morbidities. Methods: This is a retrospective study conducted in tertiary care paediatric hospital from 1st March to1st June 2009. Altogether 73 babies were included in the study. Results: Male babies outnumbered females (72.6% vs. 27.4%). Only 2.4% babies were near-term. Low birth weight (LBW) babies constituted 19.2% of the study population. Clinical sepsis as defined by WHO criteria was observed in 86.3% of babies. Nearly 50% of the babies had serum bilirubin of 15-19.9 mg/dl. Most of the babies (94.5%) improved with 5.5% of mortality. Conclusions: Hyperbilirubinaemia is one of the most common causes of hospital admission in our nursery and it is associated with various other clinical morbidities. Phototherapy is effective in most of the time, but exchange transfusion should also be carried out when phototherapy fails. Causes of hyperbilirubinaemia should be searched extensively especially to rule out haemolysis Key words: Hyperbilirubinaemia, kernicterus, neonates, phototherapy DOI: 10.3126/joim.v31i3.2990 Journal of Institute of Medicine, December, 2009; 31(3) 17-20